Do, but don't tell: The search for social responsibility and sustainability in the websites of the top-100 US MBA programs. Issue 5 (7th September 2015) - Hart, Timothy A.; Fox, Corey J.; Ede, Kenneth F.; Korstad, John
Abstract : Purpose: – The purpose of this study is to investigate the degree to which business schools, in particular MBA programs, have developed academic programs and centers specifically focused on corporate social responsibility and sustainability (CSRS) and, for those that have, promote them on their Web sites. The instruction of CSRS in institutions of higher education is increasing worldwide. The extent to which US MBA programs have developed academic programs and centers focused on CSRS could potentially be a way for business schools to distinguish themselves from other schools. Design/methodology/approach: – The authors use a Web-based search of the Web sites of the top-100 US MBA programs to ascertain the extent to which they have developed CSRS-related academic programs and centers. They then look specifically at the full-time MBA main Web page to ascertain to what extent these programs promote CSRS material. Findings: – The results suggest that schools in the top quarter and bottom quarter, as well as private schools, are more likely to have CSRS academic programs and centers. The authors also find that very few full-time MBA programs promote CSRS on their main MBA Web pages. Originality/value: – This study is unique in its focus on the top-100 US MBA programs and the collection of primary data directly from their Web sites. Additionally, a summary of the data gathered from the MBA programs is provided in Table I of the study.